Appropriate Sequence for Afatinib and Cisplatin Combination Improves Anticancer Activity in Head and Neck Squamous Cell Carcinoma - Longton, Eleonore; Schmit, Kathleen; Fransolet, Maude; Clement, François; Michiels, Carine (Frontiers in Oncology, 2018)
Despite a better understanding in head and neck tumors pathogenesis as well as improvements in radiotherapy and surgery, locally advanced head and neck squamous cell carcinoma (HNSCC) remains of poor prognosis. One promising target is the epidermal growth factor receptor (EGFR), which is overexpressed in the majority of HNSCC and is associated to tumor progression and resistance to treatment. However, in several clinical trials, the combination of EGFR inhibitors with chemotherapy and/or radiotherapy generates moderate results. In this study, we investigated the anti-tumor activity of afatinib, an irreversible pan-EGFR inhibitor, combined to cisplatin in different schedules of exposure. For that, we used two human EGFR wild-type HNSCC cell lines and we evaluated the cytotoxicity of the two drugs combined in different sequences. The efficiency of each strategy was assessed by evaluating the effects on cell cycle distribution, DNA damage, cell death and downstream pathways of ErbB family receptors. We demonstrated that cisplatin treatment followed by afatinib exposure displayed more cytotoxic effects than the opposite timing or than simultaneous association. This higher anticancer activity is probably due to inhibition of growth factor signaling on cell cycle that prevents the conversion of cisplatin adducts into DNA damage. These data suggest the importance of an appropriate timing of administration of an EGFR inhibitor and a conventional chemotherapy in order to obtain the best clinical benefit for patients with a head and neck cancer.